Clinical staging for youth at‐risk for serious mental illness. Issue 6 (22nd January 2019) - Addington, Jean; Liu, Lu; Goldstein, Benjamin I.; Wang, Jianli; Kennedy, Sidney H.; Bray, Signe; Lebel, Catherine; Stowkowy, Jacqueline; MacQueen, Glenda
Abstract : Aim: The first aim of this project was to identify a sample of youth who met different stages of risk for the development of a serious mental illness (SMI) based on a published clinical staging model. The second aim was to determine whether participants allocated to the different stages were a good fit to the model by comparing these groups on a range of clinical measures. Methods: This two‐site longitudinal study recruited 243 youth, ages 12 to 25. The sample included (a) 42 healthy controls, (b) 43 non‐help seeking individuals with no mental illness but with some risk of SMI, such as having a first‐degree relative with a SMI (stage 0), (c) 52 help‐seeking youth experiencing distress and possibly mild symptoms of anxiety or depression (stage 1a) and (d) 108 youth with attenuated symptoms of SMI, such as bipolar disorder or psychosis (stage 1b). Participants completed a range of measures assessing depression, anxiety, mania, suicide ideation, attenuated psychotic symptoms, negative symptoms, anhedonia and beliefs about oneself. Results: There were no clinical differences between HCs and participants in stage 0. For most of the clinical measures, participants in stage 1b had more severe ratings than participants in stages 1a and 0 and HCs; those in stage 1a had more severe ratings than HCs and stage 0 participants. Conclusions: These results suggest that the staging process used to allocate participants to various stages is a good fit. That is, the clinical ratings followed an ordering effect consistent with that hypothesized in the staging model.